First report of mecC MRSA in human samples from Austria: molecular characteristics and clinical data. (January 2015) - Kerschner, H.; Harrison, E.M.; Hartl, R.; Holmes, M.A.; Apfalter, P.
Abstract: Reports of mecC methicillin-resistant Staphylococcus aureus (MRSA) strains have been published from several European countries. We describe the first six mecC MRSA isolates of human origin from Austria and report the application of a rapid PCR test. Candidate isolates ( n  = 295) received between 2009 and 2013 were investigated phenotypically by cefoxitin screening and streaking on ChromID MRSA plates. The presence of mecC was confirmed in six isolates from blood cultures, wound swabs and screening samples of four female and two male patients (age range 7–89 years) by an in-house PCR method and the new Genspeed MRSA test (Greiner Bio-One, Kremsmünster, Austria). The mecC MRSA were further characterized by whole genome sequencing, multilocus sequence and spa typing. Antimicrobial susceptibility testing was performed by Eucast disk-diffusion method and Vitek 2. The six mecC MRSA isolates were from two clonal lineages (CC130, including a new single-locus variant, and CC599) and four different spa types (t843, t1535, t3256, t5930). Analysis for virulence factor genes yielded lukED, eta, etd2 and edin-B (CC130 isolates) and tst, lukED, eta and sel (ST599 isolates). The Genspeed MRSA test identified mecC in all isolates whereas Vitek 2 failed to detect methicillin resistance in one isolate. The strains were susceptible to a wide range of non-β-lactam antibiotics. All patients were successfully treated or decolonized. mecC MRSA are present in Austria as colonizers but may also cause infections. Thus, laboratories must choose appropriate test methods such as cefoxitin screening and confirmation using molecular assays specifically targeting mecC .